2013
DOI: 10.1177/1753944713476363
|View full text |Cite
|
Sign up to set email alerts
|

Exercise testing in hypertensive patients for assessing the cardiovascular protective potential of antihypertensive drugs

Abstract: Exercise testing is an established noninvasive tool in cardiology used to diagnose and guide treatment in individuals with suspected or confirmed coronary artery disease. Owing to the wealth of information it provides, exercise testing is also being utilized to evaluate prehypertensive stages, characterize hypertension, assess tolerance to exercise and the efficacy of antihypertensive therapies, and predict target organ damage and cardiovascular risk. The literature on exercise tolerance tests is relatively li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 75 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…It is well recognized that both in animal models and in humans, cardiovascular diseases are often associated with distinct skeletal muscle alterations regarding function and metabolism. 2,3,5,51 In EDL and soleus of SHR animals, a series of muscle alterations were found, indicating a form of mild myopathy. 6,7,11,14 Herein, we demonstrated that hypertension causes a phenotype-dependent dysregulation of skeletal muscle calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that both in animal models and in humans, cardiovascular diseases are often associated with distinct skeletal muscle alterations regarding function and metabolism. 2,3,5,51 In EDL and soleus of SHR animals, a series of muscle alterations were found, indicating a form of mild myopathy. 6,7,11,14 Herein, we demonstrated that hypertension causes a phenotype-dependent dysregulation of skeletal muscle calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%